2003
DOI: 10.1128/jvi.77.23.12617-12629.2003
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic Reticulum Stress Is a Determinant of Retrovirus-Induced Spongiform Neurodegeneration

Abstract: FrCasE is a mouse retrovirus that causes a fatal noninflammatory spongiform neurodegenerative disease with pathological features strikingly similar to those induced by transmissible spongiform encephalopathy (TSE) agents. Neurovirulence is determined by the sequence of the viral envelope protein, though the specific role of this protein in disease pathogenesis is not known. In the present study, we compared host gene expression in the brain stems of mice infected with either FrCas E or the avirulent virus F43,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
86
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(87 citation statements)
references
References 61 publications
1
86
0
Order By: Relevance
“…Similarly, previous studies with FrCas E -or scrapie-infected mice have shown that there is no clear correlation between the expression of GRP78 and the development of ER stress-mediated neurodegeneration. 40,41 These combined results indicate that GRP78 may be increased early after infection, but, under the conditions of prolonged ER stress in late stages of diseases, the induction of GRP78 may not be as efficient as those of other ER stress markers. Such levels of GRP78 induction may not be sufficient to protect neurons against ER stress in ts1-, FrCas E -, or scrapie-infected mice, since GRP78 overexpression protects cellular death under ER stress conditions by stabilizing Ca 2 þ homeostasis.…”
Section: Discussionmentioning
confidence: 86%
“…Similarly, previous studies with FrCas E -or scrapie-infected mice have shown that there is no clear correlation between the expression of GRP78 and the development of ER stress-mediated neurodegeneration. 40,41 These combined results indicate that GRP78 may be increased early after infection, but, under the conditions of prolonged ER stress in late stages of diseases, the induction of GRP78 may not be as efficient as those of other ER stress markers. Such levels of GRP78 induction may not be sufficient to protect neurons against ER stress in ts1-, FrCas E -, or scrapie-infected mice, since GRP78 overexpression protects cellular death under ER stress conditions by stabilizing Ca 2 þ homeostasis.…”
Section: Discussionmentioning
confidence: 86%
“…It has been shown that cell killing by pathogenic retroviruses such as FeLV-FAIDS, ts-1 MoMLV, MuLV-NT40, and FrCas E MLV strongly correlates with the inefficient processing of the precursor Env glycoprotein, resulting in its intracellular accumulation in a cell type-specific manner (11,15,21,25). A recent study of the neurovirulent FrCas E MLV further showed that the accumulation of gPr80 env activated endoplasmic reticulum (ER) stress in virus-infected microglial cells (3). Because prolonged ER stress can result in apoptosis (24), we undertook this study to determine whether a similar mechanism is functioning in the induction of cell killing by MCF13 MLV.…”
mentioning
confidence: 99%
“…The protein gp70 was observed primarily in the brains of rats infected with R7f and Rec5. It has been reported that the accumulation of uncleaved envelope precursor protein (gpr85), or the presence of Env protein with differential processing of N-linked sugar, as found in the cells infected by neuropathogenic MLVs, is an important factor in manifestation of spongiosis (3,7,8,13,14). In this study, we did not observe an abundance of gpr85 or Env with differential processing of N-linked sugar in the brains of R7f-infected rats (Fig.…”
mentioning
confidence: 99%
“…Some uninfected neurons exhibit cytopathogenicity in the brains of rats infected with neuropathogenic viruses, indicating an indirect mechanism for MLV-induced neuropathogenicity (11,18). It has been suggested that the uncleaved Env precursor protein, or Env protein with differential processing of N-linked sugar, is correlated with retrovirus-induced spongiform neurodegeneration (3,7,8,13,14). However, the pathomechanism of spongiosis induced by Env is still not understood.…”
mentioning
confidence: 99%